2000
DOI: 10.1074/jbc.m005139200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface-bound Collagenase-1 and Focal Substrate Degradation Stimulate the Rear Release of Motile Vascular Smooth Muscle Cells

Abstract: To migrate in the vessel wall, smooth muscle cells (SMCs) must contend with abundant type I collagen. We investigated the mechanisms used by human SMCs to efficiently migrate on type I collagen, following stimulation with fibroblast growth factor-2 (FGF-2). FGF-2-stimulated migration was inhibited by a hydroxamic acid inhibitor of matrix metalloproteinases and by a neutralizing anti-collagenase-1 antibody. Moreover, migration speed of SMCs plated on mutant collagenase-resistant type I collagen was not increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…These findings suggest a role for collagen cleavage in loosening cell-substrate connections to allow the cell body and tail to efficiently and appropriately follow the leading edge. Previous studies 22,34 have suggested that products of type I collagen cleavage may be promigratory. Collagen cleavage might also be important for ensuring that other promigratory matrix molecules, such as minor collagens or fibronectin, can appropriately interact with the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest a role for collagen cleavage in loosening cell-substrate connections to allow the cell body and tail to efficiently and appropriately follow the leading edge. Previous studies 22,34 have suggested that products of type I collagen cleavage may be promigratory. Collagen cleavage might also be important for ensuring that other promigratory matrix molecules, such as minor collagens or fibronectin, can appropriately interact with the cell.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Cells plated onto dishes coated with a polymerized 3D network of mouse tail collagen (0.8 mg/mL) were imaged with an inverted microscope (Zeiss Axiovert S100; Cornwall, ON, Canada or Leica DMI6000 B; Concord, ON, Canada) using modulated contrast optics. Images were digitally acquired every 5 minutes during a 6-to 8-hour recording period, using a high-resolution charge-coupled device camera (Sony XC-75/75CE; EMPIX Imaging, Inc. or Leica DFC420 C video camera; Leica Microsystems Canada, Inc.) and time-lapse software (Northern Eclipse, Empix Imaging, Inc., and Leica Application Suite; Leica Microsystems Canada Inc.).…”
Section: Migration Analysismentioning
confidence: 99%
“…47 Moreover, the composition of the collagen fibrils influences the migration properties of the SMCs, which is associated with a different focal adhesion composition and integrin function. 48 Just as fibrillar collagen type I, collagen type IV and laminin have been shown to promote the contractile phenotype. 49 However, laminin-5 was also reported to enhance PDGF-B-stimulated SMC proliferation and migration, 50 providing another example of a protein with ambiguous effects on SMC phenotype.…”
Section: Extracellular Matrix Componentsmentioning
confidence: 99%
“…Reverse migration to the wound edge is prevented by turning a pro-migratory substrate into a poor migratory substrate (19). Interestingly, a recent report suggested that MMP-1 bound to the surface of smooth muscle cells is important for stimulating migration by enhancing rear release of the integrin from the degraded collagen (42). Although this work did not determine whether the MMP-1 was bound to the ␣ 2 ␤ 1 or ␣ 1 ␤ 1 integrins, the finding is entirely consistent with the model we have presented in this report.…”
Section: Figmentioning
confidence: 99%